Para a família do Brasil: o cultivo do corpo e a diversão em Belo Horizonte nas páginas da revista Alterosa (1939 1945) - Gelka Arruda de Barros (2018)
This thesis aimed to investigate the changes of the social life of Belo Horizonte during the process of modernization of the city through the analysis of the discursive strategies present in the magazine Alterosa during the period of 1939-1945. The methodology used combined image and text content analysis. The choice of this model sought to capture the processes of meaning production in the social practices materialized in the magazine. The illustrated periodical, created in Belo Horizonte in August 1939, was an important propagator of the ideal of modernity that was sought to develop in that period, in which the capital of Minas Gerais experienced intense transformations that led to the development of a new social dynamic in the city. The national context was marked by the nationalist project of the Estado Novo and the narrowing of relations between Brazil and the United States through the "Good Neighbor Policy" aimed at achieving the country's alignment with the US war effort. This propagandistic scenario was mainly composed of the mass media, among them, the cinema that radiated the American culture as a reference of modernity, but the press was equally important to display photographs profusely, affirming a certain visuality in the urban culture of the city. This process sought to affirm habits and reconfigure behaviors under the logic of efficiency, in which the conjugal family gained centrality as a strategic place to institute social order. Thus the female body pattern was redefined aiming at healthy motherhood for the betterment of the race, while the male body was regulated aiming at its adequacy to work for the nation's progress. Together with the control of bodies, the discourse of modernity valued fun and cultivation of the body as modern practices.